Open achilles tendon rupture: a review of 33 cases - Che Ahmad, Aminudin; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Khalid, Kamarul Ariffin (2006)
Background: Achilles tendon rupture is not uncommon injury, however, the incident of open Achilles tendon injury is frequently reported. It is generally perceived that open Achilles tendon injury is associated with a poor outcome and severe complication. Objective: To study the demographic feature of open Achilles tendon injury and their functional outcome following surgical intervention. Methodology: A retrospective investigation was done at Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang from January 2001 until December 2005. Universal sampling was used t include all open Achilles tendon rupture cases we reviewed the records of these patients as well as performing clinical assessment on them. We reviewed the demographic data, the etiology of the injury and the functional outcome using the Olerud and Molande scoring system. Patients were asked about satisfaction to the current condition either through the telephone or during follow-up. Results: 33 patients were available for review (26 male and 7 female patients). Their age ranged from 12 to 58 years old. Toilet bowl injury is the most common cause of these open injury (23 cases, 68%) followed by motor vehicle accidents (6 cases, 21%). Excellent and good outcome were achieved in 69% cases. Conclusion: Operative treatment of open Achilles tendon ruptures restores sufficient ankle function and a significant percentage of patients has excellent and good outcome. Early intervention, proper debridement and good antibiotic coverage are important to ensure the outcome. Some sort of prevention is required to reduce the rate of toilet bowl injuries resulting in open Achilles tendon injuries.